Bacterial communities and soil functionality in artificially remediated vegetation of the three gorges reservoir zone - Naz, Farkhanada; Arif, Muhammad; Xue, Tan; Chen, Yangyi; Khan, Shahid Ullah; Changxiao, Li (Frontiers in Plant Science, 2025)
Riparian zones maintain biodiversity, cyclic nutrients, and regulate water quality. However, their stability is increasingly threatened by human activities such as dam construction and climate variability. This study focuses on the riparian zones of the Three Gorges Dam Reservoir (TGDR), a region marked by fluctuating water levels and a subtropical southeast monsoon climate. We investigated the seasonal and vegetation-specific dynamics of soil properties and microbial communities in riparian zones dominated by artificially remediated plants (ARPs) in the TGDR. The selected ARP species included the herbaceous Cynodon dactylon (CD) and Hemarthria altissima (HA), known for their capacity for rapid soil stabilization, and the tree species Salix matsudana (SM) and Taxodium distichum (TD), which enhance nutrient cycling through litter inputs and root exudates. These species were evaluated across spring (T1), summer (T2), and autumn (T3). Our analysis of 360 soil samples led to the generation of high-quality sequences that provided insights into microbial diversity. Principal component analysis identified organic matter, ammonium nitrogen, and total nitrogen as the main contributors to soil property variance, explaining 53.68% in T1, 51.52% in T2, and 56.37% in T3 of the variance (p < 0.01). Correlation analysis highlighted a positive relationship between soil pH and Nitrospirae (r = 0.603) and Proteobacteria (r = 0.558). Enzyme activity varied by season, with acid phosphatase activity peaking in T3 and invertase activity highest in T1. This study also made functional predictions and identified pathways pertinent to metabolism, genetic information processing, and environmental signal transduction. There were seasonal shifts in metabolic pathways, such as an increase in carbohydrate metabolism in T3 via TD. In addition, there was a rise in amino acid metabolism in T3 via CD. Our assessment of microbial diversity uncovered 68 bacterial phyla, with Proteobacteria and Acidobacteria emerging as the dominant taxa. The results indicate that ARPs positively influence microbial health, nutrient cycling, and overall ecosystem integrity. These findings hold significant implications for riparian ecosystem restoration in regions experiencing environmental changes.